PENGARUH PELATIHAN, DESKRIPSI PEKERJAAN DAN PENGEMBANGAN KARIR TERHADAP PRESTASI KERJA PEGAWAI DINAS KOPERASI DAN USAHA MIKRO KECIL DAN MENENGAH KOTA MALANG - -, Limgiani -; -, Klemen Mere (Manajemen & Bisnis Jurnal, 2016)
Abstract. Empowering Cooperatives and Micro, Small and Medium Enterprises is an integral part of the National Development and became a strategic step in improving and strengthening the basis of economic life. Thus the development of cooperatives and SMEs is a priority and become very urgent and vital. Under these conditions an employee is required to continue to hone and emningkatkan his work, thus impacting positively on the performance of employees. The purpose of this study to see the effect of simultaneous and partial training, employment and career development desripsi on the performance of staff at the Department of Cooperatives and Small and Medium Enterprises Malang. Samples are 49 respondents who are employees of Department of Cooperatives and Micro, Small and Medium Malang. The analysis used multiple linear regression. The results showed that simultaneous and partial training, employment and career development desripsi on the performance of staff at the Department of Cooperatives and Small and Medium Enterprises Malang. While the dominant variable career development is the most dominant variable affecting the work performance of employees. Keywords: Effects of Training, Job Description, Career Development, Employee Job